Comparative evaluation of denosumab efficacy of in patients with rheumatoid arthritis and postmenopausal osteoporosis: results of 1-year study in clinical practice - O. V. Dobrovolskaya; P. S. Kovalenko; N. V. Toroptsova; I. S. Dydykina; O. A. Nikitinskaya; E. L. Nasonov (Научно-практическая ревматология, 2019)
Objective: to assess bone mineral density (BMD) changes in rheumatoid arthritis (RA) patients with osteoporosis (OP) and in women with postmenopausal OP during therapy with denosumab (DSB) for 1 yearSubjects and methods. 121 women were included: the main group – 69 patients with RA (mean age – 60±7 years), 34 (49.3%) from them received glucocorticoids (GC). Comparison group comprised 52 women with primary OP (mean age – 62±10 years). Measurement of BMD using dual-energy X-ray absorptiometry (DXA) was performed in the lumbar spine (LI–IV), femoral neck (FN), proximal femur as a whole (PF) and distal forearm (DF). DSB was administered subcutaneously at a dose of 60 mg 1 time in 6 months.Results and discussion. In patients with RA, the average increase of BMD for 12 months of treatment was: in LI–IV – 4.6%, in FN-2.8%, in PF-3.0% and in DF-0.7%, and in the comparison group – 5.2; 2.1; 2.9 and 0.9%, respectively. There were no significant differences of BMD changes between the groups. Efficacy of DSB therapy in RA patients with OP did not depend on RA activity, duration of GC therapy and cumulative dose of GC. Adverse events that did not lead to the withdrawal of the drug were noted in 3% of the study participants. There were no fractures during the observation.Conclusion. The efficacy treatment with DSB for 1 year in RA patients with OP and in women with postmenopausal OP is comparable. The use of GC did not have a negative impact on DSB effect.